Genome-wide analyses of platinum-induced ototoxicity in childhood cancer patients: Results of GO-CAT and United Kingdom MAGIC consortia - Hurkmans, Evelien G. E.; Klumpers, Marije J.; Dello Russo, Cinzia; De Witte, Ward; Guchelaar, Henk-Jan; Gelderblom, Hans; Cleton-Jansen, Anne-Marie; Vermeulen, Sita H.; Kaal, Suzanne; van der Graaf, Winette T. A.; Flucke, Uta; Gidding, Corrie E. M.; et al. (Frontiers in Pharmacology, 2023)
Hearing loss (ototoxicity) is a major adverse effect of cisplatin and carboplatin chemotherapy. The aim of this study is to identify novel genetic variants that play a role in platinum-induced ototoxicity. Therefore, a genome-wide association study was performed in the Genetics of Childhood Cancer Treatment (GO-CAT) cohort (n = 261) and the United Kingdom Molecular Genetics of Adverse Drug Reactions in Children Study (UK MAGIC) cohort (n = 248). Results of both cohorts were combined in a meta-analysis. In primary analysis, patients with SIOP Boston Ototoxicity Scale grade ≥1 were considered cases, and patients with grade 0 were controls. Variants with a p-value < 10-5 were replicated in previously published data by the PanCareLIFE cohort (n = 390). No genome-wide significant associations were found, but variants in TSPAN5, RBBP4P5, AC010090.1 and RNU6-38P were suggestively associated with platinum-induced ototoxicity. The lowest p-value was found for rs7671702 in TSPAN5 (odds ratio 2.0 (95% confidence interval 1.5 – 2.7), p-value 5.0 × 10-7). None of the associations were significant in the replication cohort, although the effect directions were consistent among all cohorts. Validation and functional understanding of these genetic variants could lead to more insights in the development of platinum-induced ototoxicity.